Why do Industry and University Work Together? The Case of Li2U - Bakar, Mohd Zamri Abu; Halif, Mazuin Mat; Abd Rahim, Nur Najjah; Hassan, Mohd Faizul; Muhamed, Ariff Azly (Advances in Social Sciences Research Journal, 2024)
This paper explores the dynamics and outcomes of university-industry collaboration (UIC) in the development of a mobile application, "Li2U", designed to bridge the gap between academic learning and professional practice. The study employs an existing academic literature analysis and case study methodology to analyze the impacts of this collaboration to examine university-industry collaboration. The study delves into the collaborative process, highlighting the roles and contributions of academic researchers, and industry professionals in the app’s development. The objective of Li2U is to streamline the internship and job placement process for university students while providing employers with a reliable platform for talent acquisition and student profiling. This paper contributes to the growing body of literature on effective university-industry partnerships, offering insights into best practices and the potential for such collaborations to facilitate meaningful educational and economic outcomes. The case of Li2U serves as a model for similar initiatives, underlining the importance of aligning educational programs with industry needs and emerging technological trends